Optimization design of sphere‐tube‐coupled photoacoustic cell and application of nitrogen dioxide detection. Issue 5 (1st June 2022) - Li, Zhengang; Liu, Jiaxiang; Si, Ganshang; Ning, Zhiqiang; Fang, Yonghua; Pan, Ying
Abstract: Based on photoacoustic spectroscopy, a high‐sensitivity sphere‐tube‐coupled photoacoustic cell suitable for gas detection in the ultraviolet to the near‐infrared band (UV‐NIR) was developed. A diffuse reflection sphere with the inner wall coated with polytetrafluoroethylene (PTFE) was invoked as a long optical path cell, and the light beam was reflected multiple times on the inner wall of the sphere to increase the absorption path of the gas. An aluminum tube was used as a resonance cavity, which worked in the first‐order longitudinal resonance mode to amplify the photoacoustic signal. To improve the performance of the photoacoustic cell and the detection ability of the gas to be measured, the geometric parameters of the photoacoustic cell were optimized through finite element simulation, which not only reduced the volume of the photoacoustic cell but also increased the sound pressure and quality factor. To compare the detection performance of the photoacoustic cell before and after optimization, relevant experiments were carried out with nitrogen dioxide (NO2 ) as an example. The results showed that the response capacity of the photoacoustic cell for NO2 increased from 0.52546 to 0.61294 mV/ppm. The minimum detection limit was reduced from 270 to 68 ppt, and the average time of Allan deviation was 100 s. Additionally, due to the wide band high reflectance of PTFE, the gases with absorption peaks in UV‐NIR could realize high‐sensitivity detection based on the long optical path and acoustic resonance.